PENGARUH KUALITAS PELAYANAN DAN KEMUDAHAN TRANSAKSI PENGGUNAAN MOBILE BANKING TERHADAP KEPUASAN NASABAH BANK SYARIAH INDONESIA (BSI) KANTOR CABANG PEMBANTU (KCP) UNIVERSITAS SYIAH KUALA (USK) 1 BANDA ACEH - Maulida, Zenitha; Ridha, Ainul; Nurbismi, Nurbismi; Ivana, Farah; Ramli, Muhammad Ridha (Jurnal Sains Riset, 2024)
The aim of this research is to determine the influence of service quality and ease of transactions in using Mobile Banking on Customer Satisfaction at Bank Syariah Indonesia (BSI) Sub Branch Office (KCP) Syiah Kuala University (USK) 1 Banda Aceh. The total sample for this research was 100 respondents. The analysis used in this research is multiple linear regression analysis, and hypothesis testing is carried out using the t test (partial) and F test (simultaneous) which aims to determine partially and simultaneously the influence of the independent variable on the dependent variable at a confidence level of 95% (α = 0.05). The results of research based on tests, both partial and simultaneous, explain that there is a significant influence of service quality variables and ease of transactions on customer satisfaction at BSI KCP USK 1 Banda Aceh.Keywords : Service quality, ease of transaction, mobile banking, customer satisfaction